RELEVANSI STATUS SOSIAL EKONOMI ORANG TUA DENGAN MOTIVASI BELAJAR; SEBUAH ANALISIS LINGKUNGAN BOARDING SCHOOL - Chusnul Muali; Lana Mazida (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2018)
The social and economic status of middle-upper parents is one of the factors that can spur children to be better than parents. it is embedded in the students of Boarding School. This study aims to find out how the role of social and economic status of parents in increasing student motivation in Boarding School. This study uses a qualitative-descriptive approach, the researcher presents data obtained from the results of observations and interviews directly at the Integrated Insan Middle School (Shool Boarding). The results of the study show that, parents will know how the child develops through the boarding board. not only entrust children in the dormitory, but parents also play an active role in guiding and shaping the character of children, because basically it is the duty of parents. Student learning motivation will increase if parents, teachers, and board administrators work together to be a good motivator.